2015
DOI: 10.3389/fphar.2015.00248
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular features of interaction between VEGFA and anti-angiogenic drugs used in retinal diseases: a computational approach

Abstract: Anti-angiogenic agents are biological drugs used for treatment of retinal neovascular degenerative diseases. In this study, we aimed at in silico analysis of interaction of vascular endothelial growth factor A (VEGFA), the main mediator of angiogenesis, with binding domains of anti-angiogenic agents used for treatment of retinal diseases, such as ranibizumab, bevacizumab and aflibercept. The analysis of anti-VEGF/VEGFA complexes was carried out by means of protein-protein docking and molecular dynamics (MD) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 66 publications
(83 reference statements)
0
62
0
1
Order By: Relevance
“…VEGF-A, VEGF-B, and PIGF (placental growth factor) bind to VEGFR-1 via D2 domains while VEGF-A binds to VEGFR-2 through the domains D2 and D3 [ 15 ]. Platania and colleagues studied the interactions of VEGF antagonists/VEGF-A complexes in silico and showed the differences in the interactions and affinities, although higher affinities alone do not always translate to better efficacy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-A, VEGF-B, and PIGF (placental growth factor) bind to VEGFR-1 via D2 domains while VEGF-A binds to VEGFR-2 through the domains D2 and D3 [ 15 ]. Platania and colleagues studied the interactions of VEGF antagonists/VEGF-A complexes in silico and showed the differences in the interactions and affinities, although higher affinities alone do not always translate to better efficacy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particle mesh Ewald method ( Linse and Linse, 2014 ) was used to calculate long-range electrostatic interactions. The binding free energy of inhibitors and PRMT5 was calculated by molecular mechanics generalized-born surface area (MM-GBSA) method ( Hou et al, 2010 ; Platania et al, 2015 ; Wang et al, 2017 ). A single trajectory and three time-frames protocols were adopted here.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of protein-protein interactions were also found for other diseases and disorders including serum paraoxonase 1 with high-density lipoprotein for antiatherosclerotic activity (Patra et al, 2014 ), vascular endothelial growth factor A with binding domains of anti-angiogenic agents for retinal neovascular degenerative diseases (Platania et al, 2015 ), angiotensin-converting enzyme with Angiotensin-II for hypertension (Guan et al, 2016 ), titin with T-cap/telethonin for dilated cardiomyopathy (Kumar D. T. et al, 2017 ), CC chemokine ligand 5 (CCL5) with human neutrophil peptide-1 (HNP1) for chronic inflammatory diseases (Wichapong et al, 2016 ), and ANKS6 with ANKS3 for polycystic kidney disease (Kan et al, 2016 ). In the study of CCL5 binding with human HNP1, Wichapong et al reported a correlation coefficient of r = 0.66 between experiment and MMPBSA results for different species of CCL5.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%